Indigenous oil-degrading bacteria more efficient in soil bioremediation than microbial consortium and active even in super oil-saturated soils - Ali, Nedaa; Khanafer, Majida; Al-Awadhi, Husain (Frontiers in Microbiology, 2022)
A microbial consortium of the hydrocarbonoclastic bacterial species, Actinotalea ferrariae, Arthrobacter ginsengisoli, Dietzia cinnamea, Dietzia papillomatosis and Pseudomonas songnenensis, isolated from oil-saturated desert soil did not consume more oil, in batch cultures than the individual species with the maximum oil-consumption. In oil-polluted desert soil microcosms, the rate of oil-removal in the soil samples bioaugmented with the microbial consortium was similar to the rate of oil-removal in the unbioaugmented ones through six-month bioremediation experiment. Although the hydrocarbonoclastic bacterial communities’ composition of the unbioaugmented and bioaugmented soil samples was different, the predominant bacterial species in most of the months were the same. Towards the end of the bioremediation experiment, Ar. ginsengisoli prevailed in both soil samples suggesting its important role in oil-removal. Self-cleaning proceeded in desert soil sample artificially polluted with 1, 10, 20 and 30 % crude oil and incubated at 30 °C for six months. Oil was removed effectively at rates reaching 73.6 % and 69.3 % in the soils polluted with 1 and 10 % oil concentrations, respectively, and reached 50 % in desert soils polluted with 20 and 30 % oil concentrations. The bacterial numbers increased in all soil samples from hundreds of thousands per gram soil samples at time zero to millions and tens of millions per gram soil samples after six months. It was concluded that bioaugmenting oil-polluted soil samples with microbial consortium of hydrocarbonoclastic bacterial species with high oil-removal potential did not drastically enhance oil-bioremediation and that even in super oil-saturated soils, indigenous oil-degrading bacteria will prevail and effectively contribute to oil-removal from the surrounding environment.